Nursing Care to Improve the Quality of Nursing Services - Enok Sureskiarti; Rusni Masnina; Tri Wijayanti; Fatma Zulaikha; Andri Praja; Husnia Husnia (Indonesian Journal of Global Health Research, 2021)
A nursing care standard is a model that outlines the desired level of excellence for nursing services provided to the patient. The goal of this study was to see if there was a link between nurses' performance in providing nursing care and the quality of nursing services provided at RSIA Qurrata A'yun Samarinda. The study employed descriptive correlation research in conjunction with a cross-sectional survey design. In this study, the sample consisted of inpatients at RSIA Qurrata A'yun Samarinda, with 62 respondents meeting the inclusion and exclusion criteria. The sample was drawn using a complete random sampling approach.Using a questionnaire as a data collection tool The frequency distribution was calculated using univariate analysis, and the hypotheses were evaluated using bivariate analysis using the Somers'd test. The validity testing was conducted for 30 hospitalized patients at RSIA Aisyiyah Samarinda from August 30 to October 7, 2019. The Cronbach alpha value for the nurse performance questionnaire was 0.716 in a reliability test.The Cronbach alpha value for the quality of nursing service was 0.849, and analysis using the Somers'd test resulted in a p-value of 0.001 a 0.05, meaning that H0 is rejected and Ha is accepted, with a correlation value of 0.349, having the least correlation. As a source of information and tools for guiding nurses' performance in practicing nurses in the context of improving nursing service quality and reaching the highest level of patient satisfaction.